Sectoral choices and wage differences among Nigerian public, private and self-employees - Guven-Lisaniler, Fatma; Tuna, Gulcay; Nwaka, Ikechukwu Darlington (Emerald Group Publishing Ltd, 2018)
Purpose How does wage employment differ from self-employment in Nigeria? The purpose of this paper is to explore the determinants of participation and the resulting wage differentials with respect to individual employees in self-employment, public-wage employment and private-wage employment in the Nigerian labour market. Design/methodology/approach Using the most recent cross-sectional data from the general household survey (GHS) panel for 2012/2013 wave (Nigeria National Bureau of Statistics (NBS), 2012), this paper applies the multinomial logit estimation for the sectoral choice and selectivity-corrected wage equation where appropriate. Findings Consistent with other studies in Africa, the findings confirm that the Nigerian labour market is heterogeneous. Factors affecting sectoral choices differ greatly across the analysed sectors. Education, age and geopolitical zones are observed to be the major determinants of sectoral participation. On the basis of BFG estimates, the authors find evidence of downward bias only in the public sector wages that is due to the (Bourguignon, Fournier & Gurgand) allocation of individuals with better unobservable characteristics out of the public employment into the self-employment. Consequently, the human capital variables become no longer significant in the public wage equation after correcting for selectivity bias. However, education and gender are found to be significant determinants of wages in the private and self-employment sectors. The magnitude of the gender coefficient is more negative in self-employment, which may imply a possible gender wage gap in that sector. While the North-East, North-West and South-South zones are highly statistically significantly different from zero in the public sector, only the South-South and South-West zones appear to be significant in self-employment. Hence, such zonal variables are a reflection of differences in economic incentives in Nigeria. Research limitations/implications Given the unregulated and precarious nature of employment in self-employment, adequate policies that address gender bias orientations are suggested. Originality/value This paper is one of the first that addresses sectoral choices and wage differentials among public, private and self-employment using the most recent GHS data for Nigeria.
Keywords: Wage differentials; Nigeria; Self-employment; Labour market heterogeneity; Sectoral choice and selectivity bias; Wage employment